NEED TO PRESERVE AND SUSTAIN THE BIODIVERSITY FOR FUTURE GENERATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 11 October 2016 – Crisis in sustaining the biodiversity, which currently has become a global issue, requires immediate attention to ensure that the future development of the country could be wellmanaged.